Judicial Power Principles in the Constitutions of African States - Treskov, Aleksej P.; Jamil, Ella Z.; Novikova, Alevtina E.; Samsonov, Valery N.; Zakharov, Sergey S. (Cuestiones Políticas, 2020)
The objective of the research was to study the principles of the judiciary in the constitutions of some African states. The modern constitutional development of African states is mediated by the complex history of the continent, as well as by ongoing political processes. The emergence of basic laws in these states has become the basis not only for the establishment of constitutionalism, but also for the establishment and functioning of key public authorities. According to the functional division of state power, the organization and activities of the judicial authorities are inalienable. The source of such institutionalization and organization, of course, is its constitutions. In this sense, in the framework of this work, attention is paid to research to the analysis of the principles of the judiciary in the constitutions of African states. Formal-legal, linguistic-legal and comparative-legal methodology were used, which were used together to identify the principles of the judiciary. It is concluded that the analysis carried out showed that most of the constitutional principles sought are formalized in the special structural parts of the constitutions dedicated to the court of various instances.